The influence of electronic service quality and perceived value on customer loyalty with electronic trust and customer satisfaction as mediating variables on the Agoda application - Riswanda, Aisyah Zahra; Millanyani, Heppy (Annals of Human Resource Management Research, 2025)
Purpose: This study examines how e-service quality and perceived value influence customer loyalty on Agoda, with e-trust and customer satisfaction as mediators. Although prior studies link high service quality to strong loyalty, Agoda shows otherwise, revealing a gap addressed through an integrated loyalty model. Methodology: The research adopts a quantitative approach using purposive sampling. A total of 384 respondents of Agoda users in Indonesia were surveyed through an online questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 and supplemented by Importance-Performance Map Analysis (IPMA). Results: The results reveal that e-service quality has the most substantial total effect on customer loyalty, surpassing perceived value. However, its low performance score positions it as a critical area for improvement. Both e-trust and customer satisfaction significantly mediate the relationship between the independent and dependent variables. Conclusions: Based on the problem formulation, hypotheses, results, and discussion, it can be concluded that e-service quality and perceived value influence customer loyalty on the Agoda application through e-trust and customer satisfaction as mediating variables. Limitations: This study is limited to users of the Agoda platform in Indonesia, which may reduce its generalizability to other countries or OTAs. The study provides actionable insights for OTA platforms, particularly Agoda, in designing strategies to improve loyalty through digital service enhancement and value optimization. Contribution: This study uniquely investigates the mediating role of e-trust and customer satisfaction in the Agoda context, where loyalty issues persist despite positive service perception, an area previously underexplored in OTA research. Novelty: This study highlights a novel approach by examining the mediating roles of e-trust and customer satisfaction in the relationship between e-service quality and perceived value on customer loyalty in the context of Agoda.